ILLNESS REPRESENTATION PADA PASIEN DENGAN HIPERTENSI - Andri Setyorini; Niken Setyaningrum (Jurnal Kesehatan Al-Irsyad, 2020)
Non-communicable diseases that cause the highest death in the world, one of which is hypertension. In Indonesia, the national prevalence of hypertension in the results of the 2013 Basic Health Research based on the results of blood pressure measurements by medical personnel reached 25.8%. Management of hypertension can be done in two categories, namely non-pharmacological and pharmacological. But in practice it can certainly cause boredom and stress because they have to obey the recommended diet program during his life. So that the portrayal of the patient's implicit beliefs about the illness he is suffering from or called Illness representation can influence the way the patient chooses to deal with his illness including self-management activities carried out by the patient. This study aims to determine the picture related to "Illness Representation in Patients with Hypertension. This study uses a qualitative descriptive approach to data collection using in-depth interviews, participant observation and documentation. Analysis of data using qualitative content analysis. This study produced 6 themes based on the research objectives. The resulting themes are: 1) understanding of hypertension, 2) perceived complaints, 3) causes of disease, 4) duration of illness, 5) complications that may arise, and 6) Control or treatment